Between heaven and earth: new explorations of great Biblical texts - Lohfink, Gerhard (Liturgical Press, 2022)
"In this book Gerhard Lohfink interprets a spectrum of biblical texts, some familiar, others not. He explores them in a spirit of curiosity, questions them insistently, and confronts them with the realities of our present day, from COVID-19 to the inner loneliness experienced by so many"--